Enzymatic Synthesis of Ricinoleyl Hydroxamic Acid Based on Commercial Castor Oil, Cytotoxicity Properties and Application as a New Anticancer Agent - Jahangirian H (Dove Medical Press, 2020)
Hossein Jahangirian,1 Bahram Saleh,1 Katayoon Kalantari,1 Roshanak Rafiee-Moghaddam,1 Bahareh Nikpey,2 Siavash Jahangirian,3 Thomas J Webster1 1Department of Chemical Engineering, College of Engineering, Northeastern University, Boston, MA 02115, USA; 2Department of Agronomy and Plant Breeding, Faculty of Engineering and Agriculture, Science and Research Branch, IA University, Tehran, Iran; 3Department of Agronomy, Faculty of Agriculture, IA University, Tehran, IranCorrespondence: Hossein Jahangirian; Thomas J Webster Email kamran.jahangirian@gmail.com; th.webster@neu.eduBackground: New anticancer agents that rely on natural/healthy, not synthetic/toxic, components are very much needed.Methods: Ricinoleyl hydroxamic acid (RHA) was synthesized from castor oil and hydroxylamine using Lipozyme TL IM as a catalyst. To optimize the conversion, the effects of the following parameters were investigated: type of organic solvent, period of reaction, amount of enzyme, the molar ratio of reactants and temperature. The highest conversion was obtained when the reaction was carried out under the following conditions: hexane as a solvent; reaction period of 48 hours; 120 mg of Lipozyme TL IM/3 mmol oil; HA-oil ratio of 19 mmol HA/3 mmol oil; and temperature of 40°C. The cytotoxicity of the synthesized RHA was assessed using human dermal fibroblasts (HDF), and its application towards fighting cancer was assessed using melanoma and glioblastoma cancer cells over a duration of 24 and 48 hours.Results: RHA was successfully synthesized  and it demonstrated strong anticancer activity against glioblastoma and melanoma cells at as low as a 1 μg/mL concentration while it did not demonstrate any toxicity against HDF cells.Conclusion: This is the first report on the synthesis of RHA with great potential to be used as a new anticancer agent.Keywords: ricinoleyl hydroxamic acid, enzymatic reaction, anticancer agent, biomedicine, lipozyme and castor oil